Impacts of dry swing intervention on bat speed and attack angle: an analysis of core intervention factors - Li, Hanyao; Cheng, Gang; Zhang, Tianfeng (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigated the effects of dry swing intervention using differently weighted baseball bats on bat speed and attack angles during actual swing, simulating warm-up routines. Additionally, it explored core kinematic factors impacting subsequent bat speed and attack angles.MethodsSixty-nine baseball players were allocated by stratified randomization into three groups—normal-weight, weight, and reduced-weight—within their respective age categories. Bat swing kinematics were collected using BLAST, while bodily kinematics were captured with Rebocap sensors. Differences between pre- and post-tests were analyzed, and core intervention factors were identified with an XGBoost model and SHAP-based additive explanations.ResultsNo significant bat speed differences were found, but attack angles varied significantly in the normal-weight bat group for 12–14 year-olds (p = 0.027, ES = −0.315) and university players (p = 0.018, ES = 0.456). Core kinematic indicators included hip internal rotation (p = 0.007, ES = 0.990) and inclination angle (p = 0.023, ES = 0.184) showed significant differences, including and for the 12–14 age group using normal-weight bats, and hip external rotation (p = 0.045, ES = 1.619) for the 14–16 age group using weighted bats.DiscussionPost-test attack angles were impacted by intervention elevation and inclination angles, particularly for non-long-term bats. Adolescent athletes with shorter training term should avoid weight or reduced-weight bats for warm-up swings.